Between Medicines and Nutraceuticals in the Control of Diabetes Mellitus - Park, Cheolin; Baek, Youngdu (Asian Journal of Pharmaceutical Research and Development, 2024)
Diabetes is a type of metabolic disease such as insufficient insulin secretion or poor functioning. It is characterized by high blood sugar, which increases blood glucose concentration, causes various symptoms and signs due to high blood sugar, and excrete glucose from urine.Diabetes mellitus is divided into types 1 and 2, and type 1 diabetes was previously called ’juvenile diabetes’, and it is a disease caused by the inability to produce any insulin. Type 2 diabetes, which is relatively deficient in insulin, is characterized by insulin resistance.Insulin treatment is required for type 1 diabetes, but type 2 diabetes is based on lifestyle correction and may require additional drug administration. In addition, many patients or people concerned about diabetes use dietary supplements to control their blood sugar, but because of the side effects of prescription drugs and the lack of definitive clinical trials of dietary supplements, it is important to choose wisely between prescription drugs and dietary supplements with the advice of a physician or expert to treat or prevent diabetes.